TECHNIKI OBRAZOWANIAPatterns of coronary artery atherosclerosis in CT angiography - Wasilewski, Jarosław; Miszalski-Jamka, Karol; Głowacki, Jan (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
The paper discusses the topography of atherosclerotic lesions in coronary arteries. Knowing the location is important in the evaluation of angio CT of the coronary arteries by making it easier to distinguish soft plaques from artifacts.